2014
DOI: 10.1088/2041-8205/789/2/l28
|View full text |Cite
|
Sign up to set email alerts
|

KINETIC TURBULENCE IN THE TERRESTRIAL MAGNETOSHEATH: CLUSTER OBSERVATIONS

Abstract: 13We present a first statistical study of subproton and electron scales turbulence in the 14 terrestrial magnetosheath using the Cluster Search Coil Magnetometer (SCM) 15 waveforms of the STAFF instrument measured in the frequency range [1,180] Hz. It is 16 found that clear spectral breaks exist near the electron scale, which separate two 17 power-law like frequency bands referred to as the dispersive and the electron 18 dissipation ranges. The frequencies of the breaks f b are shown to be well correlated 19wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
87
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 40 publications
24
87
0
Order By: Relevance
“…Note that other physical effects such as Landau damping Sulem et al 2016)) and intermittency corrections associated with coherent structures, such as current sheets (Boldyrev et al 2013), can also lead to steeper spectra. It should be stressed that both phenomenological arguments and numerical simulations predict a transition at d e , while observational spectra in the terrestrial magnetosheath only display a transition at ρ e (Huang et al 2014), associated with electron demagnetization. In fact, a transition at d e is more clearly observed at the level of the magnetic compressibility (Chen & Boldyrev 2017).…”
Section: Resultsmentioning
confidence: 98%
“…Note that other physical effects such as Landau damping Sulem et al 2016)) and intermittency corrections associated with coherent structures, such as current sheets (Boldyrev et al 2013), can also lead to steeper spectra. It should be stressed that both phenomenological arguments and numerical simulations predict a transition at d e , while observational spectra in the terrestrial magnetosheath only display a transition at ρ e (Huang et al 2014), associated with electron demagnetization. In fact, a transition at d e is more clearly observed at the level of the magnetic compressibility (Chen & Boldyrev 2017).…”
Section: Resultsmentioning
confidence: 98%
“…Note that when such a separation is not performed (e.g. Huang et al 2014), some care must probably be used in the interpretation of the results. Moreover, while the example shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spectra of the magnetic field from MHD to sub-ion scales in the magnetosheath have been reported by Alexandrova, Lacombe & Mangeney (2008a) using the Cluster spacecraft, and on kinetic scales by e.g. Sundkvist et al (2007) and Huang et al (2014); see also Zimbardo et al (2010) for a review on magnetic turbulence in this region. Properties of electric and magnetic spectra between ion and electron scales have been previously studied by Mangeney et al (2006) and Lacombe et al (2006), confirming that this regime can be well resolved in the magnetosheath using Cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Major differences with the solar wind do exist, however, e.g., (i) magnetosheath turbulence evolves in a 'confined' space limited by the bow shock and the magnetopause and these boundaries may influence the anisotropy of the turbulence (Sahraoui et al 2006;Yordanova et al 2008), and, (ii) in contrast to the solar wind, the fluctuations are dominated by zero-frequency compressible fluctuations (e.g., mirror modes Sahraoui et al 2006). In a recent large survey of STAFF waveform data obtained in the magnetosheath, Huang et al (2014) quantified the differences in spectral slopes found in the solar wind and magnetosheath in the magnetic energy spectra between the ion and electrons scales (see Fig. 20).…”
Section: Electron Scale Turbulencementioning
confidence: 99%
“…On the other hand, the slopes at the electron break in the two regions were generally steeper in the magnetosheath where the distribution peaks near −5.5 and slopes can be as steep as −7. A possible explanation of this discrepancy was suggested by Huang et al (2014) based on the differences in the (Kintner and Seyler 1985;Sundkvist et al 2005), shear flows (Tajima et al 1991;Rankin et al 1997), magnetic bubbles (Birn et al 2004), and reconnection (Matthaeus 1982;Matthaeus and Lamkin 1985;Hwang et al 2013). It was only with the launch of Cluster that the ability to measure directly local vorticity became possible (albeit only by using moments of the electron distribution function) by computing the spatial variation in the velocity within the volume defined by the Cluster spacecraft (see Sec.…”
Section: Electron Scale Turbulencementioning
confidence: 99%